Study the genetic variation of Kirkuk population by using mitochondrial DNA - Najeeb Ibraheem Mohamed; Yasser Hamad Hamada; Rafea Zaidan Mukhlif (International Journal of Medical Toxicology and Legal Medicine, 2025)
Geographical barriers have been recognized as significant impediments to population mobility, and these barriers may have varying effects on various genetic markers, including mitochondrial DNA (mtDNA). Thus, the current study used mitochondrial DNA and the Y chromosome to investigate the genetic variety of the Kirkuk population.The current study was conducted in the molecular laboratory in the Department of Life Sciences, College of Science, University of Kirkuk. Samples were collected during November 2022, blood samples were collected from 500 person of Kirkuk governorate include individuals who are not related, and the total number of individuals was 500 individuals, 250 males and 250 females. The results showed that the sample of the central Arab population demonstrated limited genetic diversity with few mutations and differences between individuals.The sample shows moderate to low genetic diversity, based on nucleotide diversity (Pi) and number of mutations.for original Arabs of Kirkuk, the value is very negative and indicates an increase in rare mutations compared to expectations under the genetic equilibrium model. Genetic diversity of Kurds of Erbil and Sulaymaniyah is relatively low in the sample studied, with 16 polymorphic sites and 17 total mutations. The results show relatively low genetic diversity with a significant increase in rare mutations for original Kurds of Kirkuk. The genetic diversity in the Kakai sample is moderate to high, with 92 variant sites and 96 mutations. The Turkmen of Kirkuk sample shows low genetic variation with an excess of rare mutations. Low genetic diversity may be associated with greater genetic isolation in Christian population compared to others in the region, which may lead to less genetic diversity. about the origins of Kirkuk populations, as for the Arabs of Kirkuk, it was noted that there are many origins to which the Arabs return, as cluster U appeared, which is the highest if its percentage reached 22.22%, which originated from the Middle East, followed by cluster H, which reached 12.7%, which originated from North Africa, the Middle East, Central Asia, Northern Asia. Regarding Kakai Kirkuk, it was noted that there are some origins that Kakai belongs to, as cluster U appeared, which is the highest if it reached 37.5% and its origin goes back to the Middle East. Regarding the Kurd of Kirkuk, it was noted that there are some origins that the Kurd goes back to, as cluster H appeared, which is the highest if its percentage reached 24.19%, which originated from Europe. Regarding the Turkmen of Kirkuk, it was noted that there are some origins that belong to the Turkmen, as cluster H appeared, which is the highest if its percentage reached 20%, which originated from Europe, the Middle East, Central Asia, Northern Asia. for the Christian, it was noted that there are many origins to which the Christian return, as cluster U appeared, which is the highest if its percentage reached 42.86%, which originated from the Middle East.